Hubungan Pengetahuan Covid-19 terhadap Perilaku Hidup Bersih dan Sehat (PHBS), Asupan Vitamin A dan Vitamin E Covid-19 Knowledge Relationship to Clean and Healthy Living Behavior (PHBS), Vitamin A and Vitamin E Intake - Rifatul Masrikhiyah (Poltekkes Kemenkes Semarang, 2021)
Background: The beginning of 2020 is the beginning of the outbreak of the Covid-19 virus in Indonesia specifically. COVID-19 is a new type of disease caused by coronavirus virus infection. Doing 3M (wearing a mask, washing hands and keeping your distance), doing physical activity and consuming balanced nutrition to improve the body's immune system by consuming nutritious foods including vitamin A and vitamin E is one way to prevent contracting coronavirus.Purpose: This study aims to find out the relationship of Covid-19 knowledge to clean and healthy living behavior (PHBS), intake of vitamin A and vitamin E.Method: This study uses cross sectional research design. The sample used by 30 respondents using simple random sampling technique. Statistical analysis used in hypothesis testing is to use chi-square test to determine whether or not covid-19 knowledge relationship to PHBS and intake of vitamin A and vitamin E.Result: The results of statistical analysis obtained a value of p0.05 which means there is no relationship between knowledge of covid-19 to PHBS and intake of vitamin A and Vitamin E.Conclusion: there is no relationship between the level of knowledge of covid 19 to clean and healthy living behaviors, as well as the intake of vitamin A and vitamin E in Tegalreja Village, Banjarharjo District, Brebes Regency